Motor activity as the basis of a healthy lifestyle of student youth - Griban, G. P.; Yavorska, T. Ye.; Tkachenko, P. P.; Kuvaldina, O. V.; Dikhtiarenko, Z. M.; Yeromenko, E. A.; Lytvynenko, A. M.; Hresa, N. V.; Греса, Н. В.; ORCID: http://orcid.org/0000-0002-0517-4822; Okhrimenko, I. M.; Ovcharuk, I. S.; et al. (Wiadomości Lekarskie. - 2020. - Vol. 73, Issue 6. - P. 1199-1206, 2020)
З’ясовано роль рухової активності у формуванні здорового способу життя студентської молоді в процесі фізичного виховання. Визначено відсутність у більшості студентів потреби у здоровому способі життя, відсутність знань у цій галузі, низьку активність під час виконання вимог здорового способу життя, нераціональної організації навчальної діяльності, шкідливих звичок та інших факторів, що негативно впливають на їх здоров'я. Наголошено, що сучасна система фізичного виховання у вищих навчальних закладах України не може змінити ставлення студентів до здорового способу життя. Метою фізичного виховання, окрім формування фізичних навичок та розвитку фізичних якостей учнів, має бути виховна робота, спрямована на формування позитивного ставлення до здорового способу життя.

The aim is to find out the role of motor activity in developing a healthy lifestyle of student youth in the process of physical education. The study involved 647 students, aged 18-22. The research methods are the analysis and synthesis of the literature, analysis of curricula, programs, methodological support and quality of training, questionnaires, and the methods of mathematical statistics. It is determined that the majority of the students had no need for a healthy lifestyle, the lack of knowledge in this area, low activity while performing the requirements of a healthy lifestyle, irrational organization of educational activities, bad habits and other factors that negatively affect their health. The current system of physical education in the higher education institutions of Ukraine cannot change the attitude of students to a healthy lifestyle. The purpose of physical education, in addition to the formation of physical skills and development of students’ physical qualities, should be educational work aimed at forming a positive attitude towards a healthy lifestyle.

Выяснена роль двигательной активности в формировании здорового образа жизни студенческой молодежи в процессе физического воспитания. Определены отсутствие у большинства студентов потребности в здоровом образе жизни, отсутствие знаний в этой области, низкая активность при выполнении требований здорового образа жизни, нерациональная организация учебной деятельности, вредные привычки и другие факторы, негативно влияющих на их здоровье. Отмечено, что современная система физического воспитания в высших учебных заведениях Украины не может изменить отношение студентов к здоровому образу жизни. Целью физического воспитания, кроме формирования физических навыков и развития физических качеств учащихся, должна быть воспитательная работа, направленная на формирование положительного отношения к здоровому образу жизни.
Motor activity as the basis of a healthy lifestyle of student youth / Grygoriy P. Griban, Tetiana Ye. Yavorska, Pavlo P. Tkachenko and ot. // Wiadomości Lekarskie. - 2020. - Vol. 73, Issue 6. - P. 1199-1206. -DOI: 10.36740/WLek202006123.
Keywords: Освіта. Педагогіка. Education. Pedagogy. Образование. Педагогика; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Фізична культура. Спорт. Physical Education. Sport. Физическая культура. Спорт; рухова активність; motor activity; двигательная активность; здоровий спосіб життя; healthy lifestyle; здоровый образ жизни; фізичне виховання; physical education; физическая культура; здоров'я; health; здоровье; студент; student